The effect of formoterol inhalation on endurance performance in hypobaric conditions - Riiser, A.; Tjorhom, A.; Carlsen, K.-H. (Medicine & Science in Sports & Exercise, 2006)
Introduction: Inhaled [beta]2-agonists are important therapeutic agents for the treatment of exercise-induced asthma in athletes but are restricted by international antidoping regulations.